Probability tail for linearly negative quadrant dependent random variables of partial sums and application to linear model: Inequalities for LNQD R.V of partial sums and application - Kaddour, Zoubeyr; Belguerna, Abderrahmane; Benaissa, Samir (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
In this paper, we establish a new concentration inequality and complete convergence of weighted sums for arrays of rowwise linearly negative quadrant dependent (LNQD, in short) random variables and obtain a result dealing with complete convergence of first-order autoregressive processes with identically distributed LNQD innovations.